Alterations of Gut Microbiota in Patients With Intestinal Tuberculosis That Different From Crohn’s Disease - He, Cong; Wang, Huan; Yu, Chen; Peng, Chao; Shu, Xu; Liao, Wangdi; Zhu, Zhenhua (Frontiers in Bioengineering and Biotechnology, 2021)
Intestinal tuberculosis (ITB) and Crohn’s disease (CD) are chronic inflammatory bowel disorders that are associated with dysregulated mucosal immunity. The gut microbiota plays an important role in the regulation of host immunity and inflammatory response. Although mounting evidence has linked CD with the dysbiosis of gut microbiota, the characteristic profiles of mucosal bacteria in ITB remain unclear. The aim of this study was to assess the alterations of the gut microbiota in ITB and compare the microbiol structure of ITB with CD. A total of 71 mucosal samples were collected from patients with ITB, CD and healthy controls (HC), and then 16S rRNA gene sequencing was performed. The overall composition of gut microbiota in ITB was strikingly different from HC, with the dominance of Proteobacteria and reduction of Firmicutes. Of note, the short-chain fatty acids (SCFAs) producing bacteria such as Faecalibacterium, Roseburia, Ruminococcus were decreased in ITB relative to HC, while Klebsiella and Pseudomonas were enriched. Multiple predictive functional modules were altered in ITB, including the over-representation of lipopolysaccharide biosynthesis, bacterial invasion of epithelial cells and pathogenic Escherichia coli infection that can promote inflammation. Additionally, the microbial structure in CD was distinctly different from ITB, characterized by lower alpha diversity and increased abundance of Bacteroides, Faecalibacterium, Collinsella, Klebsiella. These four bacterial markers distinguished ITB from CD with an area under the curves of 97.6%. This study established compositional and functional perturbation of gut microbiome in ITB, and suggests the potential for using gut microbiota as biomarkers to differentiate ITB from CD.